Participation of the president in the procedure of amending the constitution in the countries of the Visegrad Group - Skotnicki, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article discusses presidential participation in the constitutional amendment in the Visegrad Group countries. The presidents of Poland and Hungary have the right to initiate a constitutional amendment, while the presidents of the Czech Republic and Slovakia do not. The presidents of all four countries cannot bring amendments to laws amend laws amending the constitution. Only the President of Poland has the right to request a referendum approving a constitutional amendment of the constitution, but only in the case of when the changes concern provisions of Chapters I, II or XII. The President of Hungary, on the other hand, can ask the Constitutional Court to examine whether a constitutional amendment has been made in accordance with the procedure prescribed by the constitution. Presidents of all countries sign constitutional amendments, however, the deadline for them to do so varies greatly. Therefore, it can be concluded that the presidents of all four countries do not play a role in the constitutional amendment procedure that is based on their constitutional position.